Age of Obsidian Butte in Imperial County, California, through infrared stimulated luminescence dating of potassium feldspar from tuffaceous sediment - Schmitt, Axel Karl; Perrine, Andrew R.; Rhodes, Edward J. (California Archaeology, 2019)
Obsidian Butte is an important lithic source for obsidian and artifacts from this location are distributed across archaeological sites in southern California and adjacent parts of northern Mexico. For this study, we used drill core material for infrared stimulated luminescence (IRSL) dating of potassium feldspar extracted from tuffaceous sediment directly underlying obsidian-bearing lava from Obsidian Butte. In addition, a core sample from lacustrine sediment below the tuffaceous sedimentary unit was dated by the same method. Stratigraphically consistent ages between 2.51 ± 0.32 kilo-annum (ka) (1 sigma uncertainty; average of two tuffaceous sediment samples) and 4.39 ± 0.49 ka (lacustrine sediment sample) were obtained. This constrains the eruption and earliest availability of the lithic resource of Obsidian Butte to 490 BCE (with uncertainty limits of ±320 years at ∼68 percent confidence, and ±640 years at ∼95 percent confidence). Since then, it would have been accessible during intermittent desiccation of Lake Cahuilla. This new date redefines obsidian from Obsidian Butte as a marker for the late prehistoric period.
Gesehen am 21.08.2019